Magnesium-doped sodium-rich sodium polyvanadate material as well as preparation method and application thereof
By doping magnesium-doped sodium-polyvanadate positive electrode material with double cation defect structure between layers, the structural stability of vanadium-based positive electrode material in magnesium ion in magnesium ion batteries is solved. and the problem of low ion diffusion efficiency, high capacity and long life of magnesium ion battery positive electrode material is achieved.
Patent Information
- Application Number
- CN202411292461.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
AI Technical Summary
Vanadium-based positive electrode materials have poor kinetic performance, insufficient stability of the matrix structure during charging and discharging, and low ion diffusion efficiency in magnesium-ion batteries, resulting in low capacitance and short cycle life.
Magnesium doped with sodium-polyvanadate material, by doping magnesium ions into sodium-polyvanadate, forming interlayer double cation (Mg2+/Na+) defect structure, the material is prepared by water bath method, and control The sodium metavanadate concentration, pH value and water bath conditions can realize the preparation of magnesium-doped sodium-polyvanadate.
Improve the charge storage capacity and structural stability of sodium polyvanadate positive electrode material, enhance the electronic conductivity and ionic conductivity, significantly improve the electrochemical performance and cycle life of magnesium ion batteries, and show high capacity and long life applications. potential.
Smart Images

Figure CN119133426A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials, and specifically relates to a magnesium-doped sodium-rich sodium polyvanadate material and a preparation method and application thereof. Background Art
[0002] Under the dual challenges of energy crisis and environmental pollution, it is particularly important to develop efficient, safe and sustainable clean energy storage technology. Magnesium ion batteries have abundant resources, high theoretical volume capacity (3833mAh / cm 3 ) and low reduction potential (-2.37V vs. SHE), are becoming the research focus of the next generation of efficient energy storage systems. However, the development of magnesium-ion batteries is constrained by several key issues, the most notable of which is Mg 2+ The high charge density of Mg leads to significant interactions with the cathode materials. This interaction limits the 2+ The reversible insertion and extraction in the host lattice easily induces the polarization effect of the cathode material, resulting in the limited capacity and cycle life of magnesium-ion batteries, which has become the main obstacle to its commercialization. Therefore, the development of cathode materials with fast ion diffusion channels and high reversibility is the key to solving this challenge.
[0003] Vanadium-based cathode materials, such as vanadium oxide, vanadium sulfide, and vanadate, are widely used in metal ion batteries due to their high theoretical capacity associated with multivalent vanadium and large interlayer spacing / tunnel structure that can accommodate magnesium ion insertion / deintercalation. However, these materials have problems such as insufficient structural stability and low ion diffusion efficiency. In order to improve the electrochemical performance of vanadium-based cathode materials, the use of ion or molecular intercalation / doping is an effective strategy. For example, CN202210207218.9 prepared a phytic acid intercalated polypyrrole@vanadate composite cathode material by a hydrothermal method and applied it to zinc ion batteries. The material has a good electrochemical performance at 5.0Ag -1 After 1,000 cycles at a high current density, the discharge capacity is still as high as 132.6 mAh g -1 , with almost no attenuation compared to the initial capacity, showing excellent cycle stability. However, during the charge and discharge cycle, the binding between the dopant and the matrix lattice is relatively weak, which can easily lead to irreversible dopant release. At the same time, improper doping can lead to structural collapse or interface damage, so the compatibility of doping with the matrix lattice needs to be carefully considered. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a magnesium-doped sodium-rich sodium polyvanadate material to solve the problems of poor kinetic performance of vanadium-based positive electrode materials in magnesium ion batteries, insufficient matrix structure stability during charge and discharge, and low ion diffusion efficiency, resulting in low capacity and short cycle life.
[0005] Furthermore, a preparation method and application of the magnesium-doped sodium-rich sodium polyvanadate positive electrode material are provided.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] A magnesium-doped sodium-rich sodium polyvanadate material, the microscopic morphology is a micron-scale porous structure, and its chemical formula is Mg x Na 2+y V6O 16 4.0H2O, of which 0 <x<0.1,0<y<6。
[0008] The preparation method of the magnesium-doped sodium-rich sodium polyvanadate material comprises the following steps:
[0009] (1) dissolving sodium metavanadate in deionized water, and stirring until the sodium metavanadate is completely dissolved to obtain a sodium metavanadate solution;
[0010] (2) adding a magnesium source to the sodium metavanadate solution and stirring evenly;
[0011] (3) adding an acid solution to the solution obtained in step (2) under stirring, and adjusting the pH to 2 to 4;
[0012] (4) placing the solution obtained in step (3) in a water bath, stirring to allow sufficient reaction, cooling naturally, filtering, washing, and drying to obtain a magnesium-doped sodium-rich sodium polyvanadate material.
[0013] Furthermore, the concentration of the sodium metavanadate solution in step (1) is 7.5 to 15 g / L. If the concentration of the sodium metavanadate solution is lower than this range, the sodium ion content is insufficient and the desired sodium-rich phase cannot be formed; conversely, if the concentration of the sodium metavanadate solution is too high, sodium metavanadate is difficult to dissolve at room temperature, affecting the doping effect.
[0014] Furthermore, in step (2), the magnesium source is one or more of magnesium sulfate, magnesium carbonate, magnesium nitrate or magnesium chloride.
[0015] Furthermore, in step (2), the molar ratio of sodium metavanadate to magnesium source is 1: 0.00045-0.02. If the magnesium source dosage is lower than this range, the magnesium dosage is too small and the performance improvement effect is poor; conversely, if the magnesium source dosage is higher than this range, it will affect the condensation process of sodium metavanadate, resulting in no precipitation product.
[0016] Furthermore, the mass concentration of the acid solution in step (3) is 5% to 30%. A low-concentration acid solution will reduce the sodium ion concentration in the original reaction solution and affect the formation of the sodium-rich phase; a high-concentration acid solution will affect the condensation process of sodium metavanadate and easily lead to impure products.
[0017] Furthermore, in step (4), the water bath temperature is 50-150°C, and the reaction time is 1-6 hours. If the temperature is not within this range, the condensation reaction rate of sodium metavanadate will be affected, resulting in poor crystallinity of the product; if the stirring time is not within this range, it may affect the magnesium source doping process, resulting in uneven magnesium ion doping. Experiments show that 6 hours is sufficient to achieve a homogeneous doping product, and no longer reaction time is required, so the preferred stirring time is 6 hours.
[0018] Furthermore, the acid solution in step (3) is one or more of sulfuric acid, nitric acid, hydrochloric acid or boric acid.
[0019] Furthermore, in step (4), the drying temperature is 60 to 100° C. and the drying time is 3 to 8 hours.
[0020] Furthermore, the pH of the solution obtained in step (3) is 2.5 to 3.5.
[0021] Furthermore, the invention provides application of the magnesium-doped sodium-rich sodium polyvanadate material in battery positive electrode materials.
[0022] The present invention adopts a simple water bath method to prepare a magnesium-doped sodium-rich-sodium polyvanadate material, which is simple, efficient and low in cost. During the specific preparation, by controlling the concentration of sodium metavanadate, the pH value of the solution and the water bath conditions, the sodium metavanadate undergoes a condensation reaction under acidic conditions to generate a corresponding phase, thereby realizing the preparation of the magnesium-doped sodium-rich-sodium polyvanadate material.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention adopts a simple water bath method to further dope magnesium ions into the sodium-rich sodium polyvanadate material to form a unique interlayer double cation (Mg 2+ / Na + ) defect structure of magnesium-doped sodium-rich sodium polyvanadate positive electrode material. Since the sodium-rich sodium polyvanadate material has good compatibility with magnesium ions and sodium ions, and the double cation defects act as pillars between layers, constraining the migration path of ions in the host structure, this stabilizes the sodium polyvanadate host structure and improves the electronic conductivity and ionic conductivity, thereby enhancing the charge storage capacity of the sodium polyvanadate positive electrode material. Further integrating this material into a magnesium full battery, the magnesium full battery exhibits excellent electrochemical performance and application potential.
[0025] 2. When the magnesium-doped sodium-rich sodium polyvanadate material is used as the positive electrode material of magnesium ion battery, at 0.05Ag -1 The specific capacity is as high as 198 mAh g -1 ; Increase the current density to 3Ag -1 The specific capacity remains at 73 mAhg -1 ; at 0.5Ag -1 The magnesium-doped sodium-rich sodium polyvanadate material and the PTCDA negative electrode were assembled into a magnesium full battery in Mg(TFSI)2 electrolyte. The full battery was tested at 0.1Ag -1 The current density was 95.7 mAh g -1 The initial discharge specific capacity is considerable, and the capacity retention rate after 300 charge and discharge cycles is 70.3%, and the average coulombic efficiency is as high as 95.5%, which shows that the magnesium-doped sodium-rich sodium polyvanadate material has a significant effect on Mg 2+ It has a high reversible storage capacity and is a highly promising high-capacity, long-life magnesium ion battery cathode material. Its excellent specific capacity and cycle performance are due to the dual cations (Mg 2+ / Na + ) defects, significantly improving the ionic conductivity, electronic conductivity and structural stability of the sodium polyvanadate material, demonstrating its great potential as a high-capacity and long-life magnesium battery positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a process flow chart for preparing the magnesium-doped sodium-rich sodium polyvanadate material of the present invention;
[0027] Figure 2 This is a SEM image of the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention;
[0028] Figure 3 This is the XRD pattern of the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention;
[0029] Figure 4 This is a TGA graph of the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention;
[0030] Figure 5 This is a graph of specific capacity at different current densities when the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention is used as the positive electrode of a magnesium ion battery;
[0031] Figure 6 When the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention is used as the positive electrode of a magnesium ion battery, at 0.5Ag -1 Long cycle test diagram under current density;
[0032] Figure 7 When the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 is used as the positive electrode of a magnesium ion battery, the -1 Long cycle test diagram under current density. DETAILED DESCRIPTION
[0033] The specific implementation modes of the present invention are further described in detail below in conjunction with specific examples.
[0034] The numerical ranges in the present invention are understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any intermediate value in the stated value or stated range and any other stated value or intermediate value in the stated range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.
[0035] Unless otherwise stated, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art described in the present invention are generally understood. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of conflict with any incorporated document, the content of this specification shall prevail. Regarding "comprising", "including", "having", "containing", etc. used herein, they are all open terms, which means including but not limited to.
[0036] Unless otherwise specified, the experimental methods used in the present invention are all conventional methods.
[0037] Unless otherwise specified, the materials, reagents, etc. used in the present invention can be purchased or synthesized by known methods.
[0038] The quantitative tests in the present invention were all repeated three times, and the results were averaged.
[0039] See also Figure 1 The preparation method of the magnesium-doped sodium-rich sodium polyvanadate material of the present invention comprises the following steps:
[0040] (1) dissolving sodium metavanadate in deionized water and stirring until the sodium metavanadate is completely dissolved;
[0041] (2) adding a magnesium source to the solution obtained in step (1) and stirring uniformly;
[0042] (3) adding an acid solution to the solution obtained in step (2) under stirring, and adjusting the pH to 2 to 4;
[0043] (4) placing the solution obtained in step (3) in a water bath, stirring to allow sufficient reaction, cooling naturally, filtering, washing, and drying to obtain a magnesium-doped sodium-rich sodium polyvanadate material.
[0044] 1. Implementation
[0045] Example 1
[0046] This embodiment provides a method for preparing a magnesium-doped sodium-rich sodium polyvanadate material, comprising the following steps:
[0047] Dissolve 30g of sodium metavanadate in 2000mL of deionized water, stir at room temperature until the sodium metavanadate is completely dissolved, then add 0.031g of Mg(NO3)2·6H2O and stir until it is completely dissolved. Subsequently, add a 10% sulfuric acid solution under stirring, adjust the pH to 2.5, and obtain a uniform orange-red transparent solution. Place the obtained uniform orange-red transparent solution in a water bath, stir at 120℃ for 2h, and filter after the reaction is completed after it is naturally cooled. The obtained precipitated product is washed three times with deionized water by suction, and placed in a drying oven at 90℃ for 6h to obtain a magnesium-doped sodium-rich-sodium polyvanadate material.
[0048] Example 2
[0049] This embodiment provides a method for preparing a magnesium-doped sodium-rich sodium polyvanadate material, comprising the following steps:
[0050] Dissolve 15g of sodium metavanadate in 2000mL of deionized water, stir at room temperature until the sodium metavanadate is completely dissolved, then add 0.031g of Mg(NO3)2·6H2O and stir until it is completely dissolved. Subsequently, add a sulfuric acid solution with a mass concentration of 15% under stirring, adjust the pH to 2, and obtain a uniform orange-red transparent solution. Place the obtained uniform orange-red transparent solution in a water bath, stir in a water bath at 60°C for 6h, and filter after the reaction is completed after it is naturally cooled. The obtained precipitated product is washed three times with deionized water by suction, and placed in a drying oven at 60°C for 8h to obtain a magnesium-doped sodium-rich-sodium polyvanadate material.
[0051] Example 3
[0052] This embodiment provides a method for preparing a magnesium-doped sodium-rich sodium polyvanadate material, comprising the following steps:
[0053] Dissolve 30g of sodium metavanadate in 2000mL of deionized water, stir at room temperature until the sodium metavanadate is completely dissolved, then add 0.062g of Mg(NO3)2·6H2O and stir until it is completely dissolved. Subsequently, add a 5% sulfuric acid solution under stirring, adjust the pH to 2.5, and obtain a uniform orange-red transparent solution. Place the obtained uniform orange-red transparent solution in a water bath, stir at 150℃ for 1h, and filter after the reaction is completed after it is naturally cooled. The obtained precipitated product is washed three times with deionized water by suction, and placed in a drying oven at 100℃ for 3h to obtain a magnesium-doped sodium-rich-sodium polyvanadate material.
[0054] Example 4
[0055] This embodiment provides a method for preparing a magnesium-doped sodium-rich sodium polyvanadate material, comprising the following steps:
[0056] Dissolve 20g of sodium metavanadate in 2000mL of deionized water, stir at room temperature until the sodium metavanadate is completely dissolved, then add 0.031g of Mg(NO3)2·6H2O and stir until it is completely dissolved. Subsequently, add a 20% sulfuric acid solution under stirring, adjust the pH to 4, and obtain a uniform orange-red transparent solution. Place the obtained uniform orange-red transparent solution in a water bath, stir at 120℃ for 2h, and filter after the reaction is completed after it is naturally cooled. The obtained precipitated product is washed three times with deionized water by suction, and placed in a drying oven at 90℃ for 6h to obtain a magnesium-doped sodium-rich-sodium polyvanadate material.
[0057] Example 5
[0058] This embodiment provides a method for preparing a magnesium-doped sodium-rich sodium polyvanadate material, comprising the following steps:
[0059] Dissolve 30g of sodium metavanadate in 2000mL of deionized water, stir at room temperature until the sodium metavanadate is completely dissolved, then add 0.031g of Mg(NO3)2·6H2O and stir until it is completely dissolved. Subsequently, add a sulfuric acid solution with a mass concentration of 15% under stirring, adjust the pH to 3, and obtain a uniform orange-red transparent solution. Place the obtained uniform orange-red transparent solution in a water bath, stir in a water bath at 100°C for 3h, and filter after the reaction is completed after it is naturally cooled. The obtained precipitated product is washed three times with deionized water by suction, and placed in a drying oven at 90°C for 6h to obtain a magnesium-doped sodium-rich-sodium polyvanadate material.
[0060] 2. Results and Analysis
[0061] (I) Structural characterization of the prepared magnesium-doped sodium-rich sodium polyvanadate material
[0062] (1) SEM characterization
[0063] See also Figure 2 , is a scanning electron microscope image (SEM image) of the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention, Figure 2 It can be seen that the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention has a micron-scale porous morphology and has abundant magnesium storage active sites.
[0064] The magnesium-doped sodium-rich sodium polyvanadate materials prepared in Examples 2 to 5 were tested in the same manner, and the results were substantially consistent with those of Example 1.
[0065] (2) XRD characterization
[0066] See also Figure 3 , is the X-ray diffraction analysis diagram (XRD diagram) of the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention, Figure 3 It can be seen that the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 is consistent with the X-ray diffraction standard card JCPDS#16-0601 (chemical formula is Na2V6O 16 ·3H2O) for comparison, the physical phases of the two are completely consistent, and the (001) crystal plane of the magnesium-doped sodium-rich-sodium polyvanadate material prepared in Example 1 of the present invention moves to a low angle, indicating the existence of interlayer cation defects.
[0067] The magnesium-doped sodium-rich sodium polyvanadate materials prepared in Examples 2 to 5 were tested in the same manner, and the results were substantially consistent with those of Example 1.
[0068] (3) TGA and ICP characterization
[0069] Figure 4 Thermogravimetric analysis (TGA) of the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 is shown in FIG. Figure 4 It can be seen that the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 contains about 4 water molecules in each product molecule.
[0070] The magnesium-doped sodium-rich sodium polyvanadate materials prepared in Examples 2 to 5 were subjected to thermogravimetric analysis, and the number of water molecules contained in each product molecule was the same as that in Example 1.
[0071] Table 1 is an ICP test result table of the magnesium-doped sodium-rich sodium polyvanadate material prepared in the present invention.
[0072] Table 1 ICP test results of magnesium-doped sodium-rich sodium polyvanadate materials
[0073]
[0074] As can be seen from Table 1, the chemical formulas of magnesium-doped sodium-rich sodium polyvanadate materials prepared in different embodiments are shown in Table 2.
[0075] Table 2 Chemical formula of magnesium-doped sodium-rich sodium polyvanadate material prepared in Example
[0076] Example Chemical formula Example 1 <![CDATA[Mg 0.02 Na 5.8 V6O 16 ·4.0H2O]]> Example 2 <![CDATA[Mg 0.02 Na 4.0 V6O 16 ·4.0H2O]]> Example 3 <![CDATA[Mg 0.04 Na 5.5 V6O 16 ·4.0H2O]]> Example 4 <![CDATA[Mg 0.02 Na 4.5 V6O 16 ·4.0H2O]]> Example 5 <![CDATA[Mg 0.03 Na 5.0 V6O 16 ·4.0H2O]]>
[0077] (II) Electrochemical performance test of magnesium-doped sodium-rich sodium polyvanadate materials
[0078] The present invention adopts the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 and loaded on a carbon paper current collector as the positive electrode; 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) is loaded on a carbon cloth current collector as the negative electrode, 1.5M Mg(TFSI)2 is used as the electrolyte, and assembled into a 2032 button cell for electrochemical performance testing. The magnesium-doped sodium-rich sodium polyvanadate positive electrode is subjected to constant current charge and discharge (GCD) test and cyclic voltammetry (CV) test using a charge and discharge test system (Neware-CT8000) and an electrochemical workstation (CHI660e).
[0079] See also Figure 5 , which is a charge and discharge diagram of the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention as the positive electrode of a magnesium ion battery at different current densities, Figure 5 It can be seen that at 0.05Ag -1 At the current density, the specific capacity of the magnesium-doped sodium-rich sodium polyvanadate cathode is as high as 198 mAh g -1 ; Increase the current density to 3Ag -1 The specific capacity of the magnesium-doped sodium-rich sodium polyvanadate positive electrode remains at 73 mAh g -1 It can be seen that the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention exhibits excellent rate performance when used as the positive electrode of a magnesium ion battery.
[0080] Figure 6 When the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention is used as the positive electrode of a magnesium ion battery, the -1 Long cycle test diagram under current density; Figure 6 It can be seen that at 0.5Ag -1 An ultra-long cycle life of 2000 times is provided at a current density. It can be seen that the magnesium-doped sodium-rich-sodium polyvanadate material prepared by the present invention has excellent long-cycle stability when used as the positive electrode of a magnesium ion battery.
[0081] Figure 7 When the magnesium-doped sodium-rich sodium polyvanadate material prepared in Example 1 of the present invention is used as the positive electrode of a magnesium ion battery, the battery has a high conductivity at 0.1Ag. -1 Long cycle test diagram under current density; Figure 7 It can be seen that the magnesium ion battery has a -1 The current density was 95.7 mAh g -1It has a considerable initial discharge specific capacity, a capacity retention rate of 70.3% after 300 charge and discharge cycles, and an average coulombic efficiency of up to 95.5%, which shows excellent electrochemical performance and practical application prospects.
[0082] It can be seen that when the magnesium-doped sodium-rich sodium polyvanadate material prepared by the present invention is used as the positive electrode material of the magnesium battery, it exhibits excellent initial specific capacity, rate performance and cycle stability, which provides a direction for the research of high-capacity and long-life magnesium secondary battery positive electrode materials.
[0083] In summary, the present invention adopts a simple water bath method to further dope magnesium ions into the sodium-rich sodium polyvanadate material to form a unique interlayer double cation (Mg 2+ / Na + ) defect structure of magnesium-doped sodium-rich sodium polyvanadate positive electrode material. Since the sodium-rich sodium polyvanadate material has good compatibility with magnesium ions and sodium ions, and the double cation defects act as pillars between layers, constraining the migration path of ions in the host structure, this stabilizes the sodium polyvanadate host structure and improves the electronic conductivity and ionic conductivity, thereby enhancing the charge storage capacity of the sodium polyvanadate positive electrode material. Further integrating this material into a magnesium full battery, the magnesium full battery exhibits excellent electrochemical performance and application potential.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A magnesium-doped sodium-rich sodium polyvanadate material, characterized in that: The microstructure is a micron-scale porous structure, and its chemical formula is Mg x Na 2+y V6O 16 4.0H2O, of which 0 <x<0.1,0<y<6。 2. The method for preparing the magnesium-doped sodium-rich sodium polyvanadate material according to claim 1, characterized in that: The following steps are involved: (1) dissolving sodium metavanadate in deionized water, and stirring until the sodium metavanadate is completely dissolved to obtain a sodium metavanadate solution; (2) adding a magnesium source to the sodium metavanadate solution and stirring evenly; (3) adding an acid solution to the solution obtained in step (2) under stirring, and adjusting the pH to 2 to 4; (4) placing the solution obtained in step (3) in a water bath, stirring to allow sufficient reaction, cooling naturally, filtering, washing, and drying to obtain a magnesium-doped sodium-rich sodium polyvanadate material.
3. The method for preparing the magnesium-doped sodium-rich sodium polyvanadate material according to claim 2, characterized in that: The concentration of the sodium metavanadate solution in step (1) is 7.5-15 g / L.
4. The method for preparing the magnesium-doped sodium-rich sodium polyvanadate material according to claim 2, characterized in that: In the step (2), the magnesium source is one or more of magnesium sulfate, magnesium carbonate, magnesium nitrate or magnesium chloride.
5. The method for preparing the magnesium-doped sodium-rich sodium polyvanadate material according to claim 2, characterized in that: In the step (2), the molar ratio of sodium metavanadate to magnesium source is 1:0.00045-0.
02.
6. The method for preparing the magnesium-doped sodium-rich sodium polyvanadate material according to claim 2, characterized in that: The mass concentration of the acid solution in step (3) is 5% to 30%.
7. The method for preparing the magnesium-doped sodium-rich sodium polyvanadate material according to claim 2, characterized in that: In the step (4), the water bath temperature is 50-150° C., and the reaction time is 1-6 hours.
8. The method for preparing the magnesium-doped sodium-rich sodium polyvanadate material according to claim 2, characterized in that: The acid solution in step (3) is one or more of sulfuric acid, nitric acid, hydrochloric acid or boric acid.
9. The method for preparing the magnesium-doped sodium-rich sodium polyvanadate material according to claim 2, characterized in that: In the step (4), the drying temperature is 60-100° C. and the drying time is 3-8 hours.
10. Use of the magnesium-doped sodium-rich sodium polyvanadate material according to claim 1 in battery positive electrode materials.
Citation Information
Cited By
Sodium-rich sodium polyvanadate material, preparation method thereof, positive plate and battery
CN119092699A
A sodium-rich sodium polyvanadate material, a preparation method thereof, and a positive plate and a battery
CN119092699B
